Rehabilitasi Sebagai Upaya Pelesterian Terumbu Karang di Wilayah Konservasi Perairan Indonesia - Arungla’bi, Yora; Kamal, Eni; Damanhuri, Harfiandri; Tebay, Selvi; Wulandari, Dwieke Putri (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Coral reef ecosystems are vulnerable to damage. This ecosystem is found in tropical and subtropical seas and consists of reefs (calcareous structures) derived from coral animals and other biota. Considering these issues, efforts are needed to find other ways to enhance the exploration of marine resources without causing damage or increasing environmental productivity. This research employs the process of literature review. The results of article searches in the identified databases show that there are various factors that cause damage to the coastal coral reef ecosystem. There are two human (anthropogenic) factors, including the dumping of garbage into the sea, the use of destructive fishing tools, the mining of corals for consumption, and the temperature, brightness, and predators of coral. The damage to the coral reef ecosystem is caused by the human factor (80.98%) compared to the natural factor (58.09%). Addressing this problem, coral reefs in Indonesia have been saved through rehabilitation and conservation using techniques such as spider web transplantation and hybrid shelves and cor, as well as developing CMRIS (Coral Reef Management Information System) and COREMAP (Coral Reef Rehabilitation and Management Programme) as technology systems.